Antioxidant Activity of Lactobacillus spp as for Development of Antioxidantive Probiotic - Komang Ayu Nocianitri; I Nengah Sujaya; Yan Ramona (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2016)
Probiotics are live microorganisms which when administered in adequate amount confer health benefit to the host. Our previous studies revealed that Lactobacillsus spp isolated from infant feces potential to be developed as probiotics. Since the functionality of probiotic is strain specific, it is worth to screen the antioxidant activity of those lactobacilli, which will be developed as antioxidative probiotic. The aim of this study was to screen antioxidant activities of Lactobacillus spp isolated from infant feces. A numbers of 20 Lactobacillus spp strains isolated from infant feces were used in this study. The antioxidant activities was determined in in vitro studies by measuring the lipid peroxidation, hydroxyl radical scavenging activity, and ferrous chelating activity. The result showed that inhibitory activity of lipid peroxidation, hydroxyl radical scavenging activity, and ferrous chelating activity exerted by of Lactobacillus spp was 10.12 - 83.02%, 16,50-46,73%, and 3.94 - 44.52%, respectively. The Lactobacillus sp FBB 60 and Lactobacillus sp FBB 81 showed the high antioxidant activity compared to the others lactobacilli. The antioxidant activity of Lactobacillus sp FBB 60 were 61,20%, 46,37%, 31,54%  and the activity of Lactobacillus sp FBB 81 were 57,01%, 29,31% 44,52 for the lipid peroxidation inhibitory activity, hydroxyl radical scavenging activity and ferrous chelating activity, respectively. This finding implied that the Lactobacillus sp FBB 60 and Lactobacillus sp FBB 81 are promising strain to be developed as antioxidative probiotic.